Formation of thermal conductive network in boron nitride/polyvinyl alcohol by ice-templated self-assembly. Issue 23 (1st December 2021) - Wu, Wenjie; Liu, Hewei; Wang, Zhongyue; Lv, Peng; Hu, Ertao; Zheng, Jiajin; Yu, Kehan; Wei, Wei
Abstract: Ceramic/resin composite is an important thermal management material for electronic packaging. The formation of a thermally conductive network of ceramic fillers in the composite is the key to improving thermal conduction performance. We design a method of ice-templated self-assembly followed by hot pressing to prepare oriented boron nitride/polyvinyl alcohol (BN/PVA) composites. First, the BN/PVA aerogel is made by freezing and then freeze-drying. BN flakes are squeezed by ice crystals to form a 3D network at the ice interfaces. After further removing the gaps between the BN flakes by hot pressing, a dense BN/PVA composite material is obtained. The resulting polymer composite has a thermal conductivity up to 10.04 W m −1 K −1 at h-BN content of 68 wt%. Theoretical analysis shows a low interfacial thermal resistance between BN flakes. This approach can potentially be used in advanced electronic packaging technology, especially in the design of thermal interface materials.